Direct oxidation of various oil palm components using CeO catalyst for vanillin production - Anita Ramli; Nur Akila Syakida Idayu Khairul Anuar; Farinaa Md Jamil; Najman Naqib Kamaruzaman; Nurazieda Dayana Rozi; Cham, Hui Jing; Farah Anis Syafiqah Md Farizal; Nur Masitah Laily Zamri (Penerbit Universiti Kebangsaan Malaysia, 2025)
Vanillin has a significant market demand as it is consumed as raw materials in many daily products such as fragrances and pharmaceuticals. The supply chain is dominated by synthetic vanillin due to its preferred pathway and cost-effective manufacturing. The different palm oil biomass feedstocks, including fronds, trunks, empty fruit bunches, kernel shells, and mesocarp fibers, were evaluated to determine which one yields the highest vanillin composition by employed CeO2 nanoparticles as catalyst. The physicochemical properties of the catalyst were characterized using X-ray diffraction, N₂ adsorption-desorption, temperature-programmed oxidation (TPO), and temperature-programmed reduction (TPR) analyses to assess the crystallinity, textural properties, and redox behavior of the CeO2 nanoparticles. The synthesized CeO2 nanoparticles showed the presence of diffraction peaks assigned to the presence of cubic fluorite. The N2 adsorption– desorption isotherms showed that all catalysts possess a Type IV isotherm, indicating a mesoporous structure. From the TPO and TPR profiles, both surface and bulk oxygen species suggest that surface oxygen vacancies play a key role in adsorbing and activating oxygen molecules, leading to a high rate of adsorbed oxygen formation. A direct oxidation method via microwave irradiation with the presence of a nanoparticle catalyst was used to assist the lignin derivation to vanillin production. A test done for all waste samples showed that mesocarp fiber gives the highest vanillin yield of at 6.74% from the direct oxidation method and 11.93% from the lignin extraction method.